Protozoa enhance foraging efficiency of arbuscular mycorrhizal fungi for mineral nitrogen from organic matter in soil to the benefit of host plants. Issue 1 (28th March 2013) - Koller, Robert; Rodriguez, Alia; Robin, Christophe; Scheu, Stefan; Bonkowski, Michael
Summary Dead organic matter (OM) is a major source of nitrogen (N) for plants. The majority of plants support N uptake by symbiosis with arbuscular mycorrhizal (AM) fungi. Mineralization of N is regulated by microfauna, in particular, protozoa grazing on bacteria. We hypothesized that AM fungi and protozoa interactively facilitate plant N nutrition from OM. In soil systems consisting of an OM patch and a root compartment, plant N uptake and consequences for plant carbon (C) allocation were investigated using stable isotopes. Protozoa mobilized N by consuming bacteria, and the mobilized N was translocated via AM fungi to the host plant. The presence of protozoa in both the OM and root compartment stimulated photosynthesis and the translocation of C from the host plant via AM fungi into the OM patch. This stimulated microbial activity in the OM patch, plant N uptake from OM and doubled plant growth. The results indicate that protozoa increase plant growth by both mobilization of N from OM and by protozoa–root interactions, resulting in increased C allocation to roots and into the rhizosphere, thereby increasing plant nutrient exploitation. Hence, mycorrhizal plants need to interact with protozoa to fully exploit N resources from OM.